VD_FINDINFO Jug / 2015 / 192 vom 22. Januar 2015 - VD Tribunal cantonal (2015)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, CONTRAVENTION, CONDAMNATION | 32 LCR, 90 al. 1 LCR, 3 al. 1 OCR, 398 al. 4 CPP (CH)